Molecular and functional characterization of pigeon (Columba livia) tumor necrosis factor receptor-associated factor 3. (April 2017) - Zhou, Yingying; Kang, Xilong; Xiong, Dan; Zhu, Shanshan; Zheng, Huijuan; Xu, Ying; Guo, Yaxin; Pan, Zhiming; Jiao, Xinan
Abstract: Tumor necrosis factor receptor-associated factor 3 (TRAF3) plays a key antiviral role by promoting type I interferon production. We cloned the pigeon TRAF3 gene ( PiTRAF3 ) according to its predicted mRNA sequence to investigate its function. The 1704-bp full-length open reading frame encodes a 567-amino acid protein. One Ring finger, two TRAF-type Zinc fingers, one Coiled coil, and one MATH domain were inferred. RT-PCR showed that PiTRAF3 was expressed in all tissues, with relatively weak expression in the heart and liver. In HEK293T cells, over-expression of wild-type, △ Ring, △ Zinc finger, and △ Coiled coil PiTRAF3, but not a △ MATH form, significantly increased IFN-β promoter activity. Zinc finger and Coiled coil domains were essential for NF-κB activation. In chicken HD11 cells, PiTRAF3 increased IFN-β promoter activity and four domains were all contributing. R848 stimulation of pigeon peripheral blood mononuclear cells and splenocytes significantly increased expression of PiTRAF3 and the inflammatory cytokine genes CCL5, IL-8, and IL-10 . These data demonstrate TRAF3's innate immune function and improve understanding of its involvement in poultry antiviral defense. Highlights: Pigeon TRAF3 was expressed in all tested tissues. The MATH domain is necessary for IFN-β promoter activation. The zinc finger and coiled coil are essential for NF-κB activation. R848 induces TRAF3 and cytokine up-regulation in pigeon PBMCs and splenocytes.